Problems of Rehabilitation and Prophylaxis of Adverse Reactions to Antiestrogen Therapy in Patients with Breast Cancer - S. V. Strazhev; P. V. Koposov; A. V. Belonogov (Антибиотики и Химиотерапия)
The principles of specific rehabilitation in females with hormone sensitive breast cancer depending on the type of the antiestrogen hormonotherapy are described. According to the different mechanisms of action of the antiestrogen blockers impact (blocking of estrogen receptors, steroid and nonsteroid aromatase inhibition) programs for rehabilitation depending on the different spectra of antiestrogen therapy side effects were designed.